Range-wide decline of Chinese giant salamanders Andrias spp. from suitable habitat. Issue 3 (24th May 2021) - Tapley, Benjamin; Turvey, Samuel T.; Chen, Shu; Wei, Gang; Xie, Feng; Yang, Jian; Liang, Zhiqiang; Tian, Haifeng; Wu, Minyao; Okada, Sumio; Wang, Jie; Lü, Jingcai; et al.
Abstract: Over recent decades, Chinese giant salamanders Andrias spp. have declined dramatically across much of their range. Overexploitation and habitat degradation have been widely cited as the cause of these declines. To investigate the relative contribution of each of these factors in driving the declines, we carried out standardized ecological and questionnaire surveys at 98 sites across the range of giant salamanders in China. We did not find any statistically significant differences between water parameters (temperature, dissolved oxygen, ammonia, nitrite, nitrate, salinity, alkalinity, hardness and flow rate) recorded at sites where giant salamanders were detected by survey teams and/or had been recently seen by local respondents, and sites where they were not detected and/or from which they had recently been extirpated. Additionally, we found direct and indirect evidence that the extraction of giant salamanders from the wild is ongoing, including within protected areas. Our results support the hypothesis that the decline of giant salamanders across China has been primarily driven by overexploitation. Data on water parameters may be informative for the establishment of conservation breeding programmes, an initiative recommended for the conservation of these species.